Determinan Audit Judgment dalam Perspektif Gender pada Pemeriksa BPK RI Perwakilan Provinsi Sumatera Selatan - Taqwinda, Ernaldi (Program Studi Akuntansi FPEB UPI, 2018)
The purpose of this study is to provide the difference in audit judgment and to determinant factors on audit judgment by female and male auditors. The research method was survey method with primary data. The samplea are auditors in South Sumatera Representative of BPK RI amounted up to 49 respondents, which consist of 33 males and 16 females. Data analysis used are mean difference analysis and multiple regression analysis. The result shows that there is a difference of audit judgment between female and male auditors. The result of multiple regression analysis on male auditors found that obidience pressure, task complexity, and experience, partially, has significant effect on audit judgment meanwhile expertise is found to have insignificant effect on audit judgment. A slightly different results are yield in investigating the female auditors that only obidience pressure and task complexity that have significant effect on audit judgment, partially. Meanwhile, experience and expertise have insignificant effect on this dependent variable.